PRAGMATIC REALIZATION OF IMPLICIT EVALUATIVE EXPRESSIONS, SUCH AS PRAISE AND COMPLIMENTS, IN ENGLISH COMMUNICATION - Eshonkulova Gulrux Turaqulovna (Journal Park Publishing, 2025)
This article investigates the pragmatic realization of implicit evaluative expressions, such as praise and compliments, in English communication. Through a qualitative analysis of conversational data, this study explores how speakers convey positive evaluations without direct, explicit statements. The research highlights the role of indirectness, politeness strategies, and cultural nuances in shaping the pragmatic use of these expressions. A comparative analysis of direct versus indirect expressions is provided, with specific examples from different communicative contexts.
Keywords: Pragmatics, implicit evaluative expressions, compliments, praise, indirectness, communication, politeness strategies.